Nye arkæologiske publikationsformer - Thrane, Henrik (Kuml, 1966)
New trends in archaeological publications A problem common to all disciplines is how to make basic material available to scholars in the best way. Nearly every archaeological publication presents new basic material, but let us here consider only the corpus publication presenting large numbers of finds with some common quality -topographical, chronological or otherwise. Many solutions have been attempted, as a few random examples will show [1]. Some publications date more quickly than others, but eventually they will all have to be supplemented or entirely rewritten. This is a quite natural process, considering the wealth of new methods that the natural sciences have given to archaeology in this century -enormous advances that could hardly have been anticipated. As examples of how the publication problem is being tackled in our generation, I have chosen two new corpus works, Inventaria Archaeologica and Index de l'outillage en bronze. While classical archaeologists and philologists have long had access to internationally edited corpus works covering different areas, such as pottery, inscriptions and coins, corresponding works covering European prehistory are largely lacking. lnventaria Archaeologica, which was started by the Belgian archaeologist M.-E. Mariën at the Archaeological Congress in Zürich in 1950 [2] is an attempt to fill that gap. The first set was pubIished in 1953 and has been followed by about 64-65 sections, each with about 10 plates of drawings. At present, lnventaria Archaeologica covers both East and West Europe, and recently the first Danish sets were published [3]. UNESCO provides financial support, and the work is under the supervision of the International Council for Philosophy and the Humanities. The idea behind this cumulative work is to publish finds of one or several artefacts, which by their association or stratigraphical context are accessible to dating, the most important being grave, settlement and hoard finds [4]. At the moment the work confines itself to the Copper, Bronze and Iron Ages. The typographical arrangement follows definite rules, but a definite model for description and illustration of artefacts is lacking, resulting in varying standards, and departures from the uniform basis for comparison which must have been the original intention. For example it is frequently a minor detail, which can only be seen in a cross-section, that determines whether two artefacts can be satisfactorily compared, and these details cannot always be derived from the drawings. Another important deficiency in lnventaria Archaeologica is not yet evident, but will appear as several thousand sheets, each with about ten quite different artefacts, have been published. The point will be reached where it will be impossible to see the wood for the trees [5]. In order to investigate the occurrence of an artefact, it will be necessary to provide a key of some sort, in which one ought to be able to ascertain quickly in what context each type occurs. The advantage of Inventaria Archaeologica over other cumulative works is its international character and the new appraisal of finds which have for years been the corner-stones of European chronology. It would obviate the necessity of searching through endless numbers of journals, if important finds with comparative dating relevance were automatically published in Inventaria. The so-called »type card reports«, which ceased publication in 1907 [6], was a publication form which dated quickly, owing to paucity of illustration and too wide a typological concept being employed. It seems that this publication form is to be revived in revised form, in an attempt to make the complete European inventory of metal artefacts of the Bronze Age accessible to scholars [7]. An experimental application of modern methods of documentation has been carried out in the last few years by a department of the French National Research Centre -the Centre for Documentary Analysis in Archaeology. Experts in statistics, data processing and archaeology have co-operated in developing systems whereby modern punched card processes and the like can be applied to archaeological material [8]. Widely divergent subjects have been treated, but so far the only one published is the classification of prehistoric metal artefacts of the Bronze Age in the area between the Indus and the Balkans in the 4th to the 2nd millennia B.C. [9]. Index de l'outillage en bronze has been compiled by the archaeologist Jean Deshayes, who has used it in his doctoral dissertation [10], and by J. C. Gardin. It consists of a catalogue with a card for each object, with a simple sketch and essential references, and a peek-a-boo card-index, which is operated simply by holding punched cards up to the light and noting the holes common to all the cards held. There are 400 cards, each covering a single typological element. (A typological element is any detail or property which can be registered objectively) [11]. There is in addition a 40-page key to the code employed in the cards and a commentary of 275 pages! New cards can be added to the catalogue without upsetting the numerical arrangement, and the punched cards permit an almost infinite combination of the 400 typological elements, which can be treated without reference to the context in which they are normally considered. One can develop one's own typology and check it by means of the punched cards. The authors of the Index have tried to employ all those criteria which alone or in combination determine a type (the constituent typological elements) [12], inasmuch as they attempt to meet the normal demands of scholars and not the complete state of knowledge [13]. The commentary, which is the most interesting part of the Index, discusses the theoretical basis for the system, the analyses and the classification adopted, gives examples of the procedure followed in analysing various types of artefacts, shows how a type is constructed from the constituent elements and includes a glossary of terms used. The basis for the classification adopted in the analysis is the function of the artefact as manifested in its functional elements (edge, point, etc.) and hafting. Fig. 4-6 illustrate the six main groups into which the analysis and description of artefacts are divided, comprising I the basic types, II the functional part, III the hafting, IV the connection between II and III, V detail and VI archaeological information. The French system aims at a standard procedure whereby any metal tool can be described according to the code, irrespective of its date and provenance. This is no doubt possible, but the resulting characterization would be too general for it to be of use in advanced typological studies. One could, for example, distinguish between a palstave and a socketed axe but not satisfy the demands made on the classification of Nordic bronze artefacts and certainly not those which will be made 10 years from now. The material on which the code is built up and which is analysed by it, is reproduced by simple line drawings on the index cards, but the frequently very poor quality of these drawings clearly illustrates a deficiency in the work. A very large proportion of the analyses have had to be based on information extracted from literature, as Deshayes was not able to examine the artefacts in question. As this information is at best inadequate, at worst misleading, these error factors are transferred to the analysis, which thereby loses some of its value and cannot be considered entirely reliable. The effort and money expended on the production of Index de l'outillage would be out of all proportion to its value, when one remembers that the material was already available in card form, and the typological conclusions drawn in Deshayes' dissertation, were it not for the fact that the Index must be intended to draw attention to the possibilities in the system and to arouse discussion and cause attitudes to be defined. Whilst Inventaria Archaeologica represents a refurbishing of a tried publication form, the French publication shows the way ahead. There is little doubt that analyses such as those described above will be the documentation form of the future for large parts of the archaeological material, and the advantages of the method are apparent where large groups of homogeneous material, such as pot sherds from large settlement finds, are involved [16]. Henrik Thrane